Pedagogy of Hope - Freire,Paulo (London Continuum, 1994)
With Pedagogy of Hope, Freire explores his best-known analytical themes - with even deeper understanding and a greater wisdom. Certainly, all of these themes have to be analyzed as elements of a body of critical, liberationist pedagogy. In the present book, we come to understand the author's pedagogical thinking even better, through the critical seriousness, humanistic objectivity, and engaged subjectivity which, in all of Freire's books, are always wedded to a unique creative innovativeness.
Keywords: 9